Biodiversity conservation status in China's growing protected areas. (June 2017) - Zhang, Lyubing; Luo, Zhenhua; Mallon, David; Li, Chunwang; Jiang, Zhigang
Abstract: The past 40 years witnessed a boom of protected areas (PAs) in China. To date, China has established 11 types of PAs, whose conservation objectives vary from protecting biodiversity and geological features, preserving scenic landscapes and seascapes, to restoring and maintaining ecosystem services. Covering over 17% of the land and 3.5% of the marine territory of China, the PAs have had beneficial effects on conservation in this country. However, the success of these PAs is largely restricted by ecological gaps in PA structure, defects of the management system, and is also negatively influenced by local development and urbanization driven by a growing economy. To improve the conservation efficiency of China's PAs, we suggest structural adjustment based on integrative research, practical strategies to alleviate administrative conflicts, increased engagement of local communities, transparent allocation of conservation funding, strengthened supervision and penalty mechanisms for destructive activities, and improved large-scale designation to coordinate demands of conservation and socioeconomic development. Highlights: China has accomplished designating 17% of its terrestrial areas as protected areas (PAs) as set in Aichi Target 11. PAs have contributed to safeguarding biodiversity and restoring ecosystem services in China. Effectiveness of China's PA network is restricted by structural and management issues, and impacts of economic development. Improvements in PA quality should be emphasized, and strategies are needed to fill ecological and management gaps.